TRAIT KEPRIBADIAN OPENNES TO EXPERIENCE DAN DIGITAL CITIZENSHIP PADA FRESH GRADUATE - Andriani, Ika Noviana; Ricca Angreini Munthe; Harmaini; Putri Miftahul Jannah (Dinamika Psikologis: Jurnal Ilmiah Psikologis, 2025)
Abstrak Perkembangan teknologi digital kerap kali menuntut individu untuk memiliki kemampuan digital citizenship yang memadai, terutama bagi para fresh graduate yang sedang memasuki dunia karier dan kehidupan sosial yang lebih kompleks. Namun, masih banyak fresh graduate yang belum bisa memanfaatkan teknologi digital dengan baik, yang menandakan rendahnya digital citizenship. Digital citizenship dipengaruhi oleh beberapa faktor, salah satunya adalah trait kepribadian openness to experience. Penelitian ini bertujuan untuk mengetahui hubungan openness to experience dengan digital citizenship pada fresh graduate di Indonesia. Sampel penelitian diambil dengan teknik snowball sampling dan melibatkan 300 partisipan. Instrumen yang digunakan yaitu skala digital citizenship (27 item, α = 0,913) dan skala openness to experience dari IPIP-BFM-50 versi Indonesia (10 item, α = 0,768). Hasil analisis korelasi Pearson menunjukkan koefisien r = 0,399 dengan p < 0,01, artinya terdapat hubungan positif yang signifikan antara openness to experience dan digital citizenship. Variabel openness to experience berkontribusi sebesar 15,9% terhadap variasi digital citizenship, sementara 84,1% dijelaskan oleh faktor lain. Penelitian ini memberikan bukti empiris bahwa karakteristik kepribadian openness to experience berperan penting dalam meningkatkan kemampuan digital citizenship fresh graduate. Kata Kunci : digital citizenship, fresh graduate, trait openness to experience Abstract The development of digital technology often requires individuals to have adequate digital citizenship skills, especially for new graduates entering a more complex career and social life. However, there are still many new graduates who are unable to utilize digital technology properly, indicating a low level of digital citizenship. Digital citizenship is influenced by several factors, one of which is the personality trait of openness to experience. This study aims to determine the relationship between openness to experience and digital citizenship among new graduates in Indonesia. The research sample was taken using the snowball sampling method and involved 300 participants. The measuring instruments used were the digital citizenship scale (27 items, α = 0.913) and the openness to experience scale from the Indonesian version of IPIP-BFM-50 (10 items, α = 0.768). The results of Pearson's correlation analysis showed a coefficient of r = 0.399 with p < 0.01, meaning that there was a significant positive relationship between openness to experience and digital citizenship. The variable of openness to experience contributed 15.9% to the variation in digital citizenship, while 84.1% was explained by other factors. This study provides empirical evidence that the personality characteristic of openness to experience plays an important role in improving the digital citizenship skills of new graduates. Keywords : digital citizenship, fresh graduate, trait openness to experience